2019
DOI: 10.1016/j.bjae.2019.07.002
|View full text |Cite|
|
Sign up to set email alerts
|

Non-regional analgesia for labour: remifentanil in obstetrics

Abstract: By reading this article, you should be able to: Explain the indications for the use of remifentanil in labour. Compare the effectiveness of remifentanil with other common practices for analgesia in labour. Discuss the safety profile of remifentanil for mother and neonate. Describe the precautions and monitoring required when giving remifentanil in labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Of note, in many studies, Remifentanil was discontinued during the seconds stage of labor for fear of neonatal depression and expert authors advocate the availability of oxygen, naloxone and pediatrician when Remifentanil PCIA is used for labor analgesia. 19 Maternal safety…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in many studies, Remifentanil was discontinued during the seconds stage of labor for fear of neonatal depression and expert authors advocate the availability of oxygen, naloxone and pediatrician when Remifentanil PCIA is used for labor analgesia. 19 Maternal safety…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have not reported duration of remifentanil administration [ 18 ]. The maternal labor experience was reported using surveys and postpartum telephone interviews on women from the RESPITE study; 30 received remifentanil IV-PCA and 19 IM meperidine [ 1 ].…”
Section: Intravenous Opioid Labor Analgesiamentioning
confidence: 99%
“…While the recommendation of 1:1 nursing increases the chance of identifying respiratory depression [18], this may not be universally available. The difficulty to provide suitable staff monitoring is further compounded in the setting of increasing numbers of deliveries and insufficient concurrent staff increases [10].…”
Section: Remifentanil Safetymentioning
confidence: 99%
“…There are also other pain management options, like the use of opioids. Remifentanil is probably the most popular among opioids because of its short-acting characteristics [ 2 ]. It serves as an alternative to epidural anesthesia when an epidural is not feasible or desired.…”
Section: Introductionmentioning
confidence: 99%